The Role of Risk Analysis in EU Food Governance: Balancing Scientific Food Safety Factors and External Factors that Inform Risk Management for Healthier Food Systems - Maria El Gemayel; Herwig C.H. Hofmann; Felix Pflücke (European Journal of Risk Regulation)
Scientific consensus links dietary choices to health outcomes, highlighting the urgency to prioritise healthy food production in food systems. At the EU level, however, defining healthy food and integrating it into food governance remains a challenge, particularly regarding the inclusion of health-related characteristics in food safety assessments. While the EU primarily relies on the risk analysis principle to address food safety concerns, the process still exhibits weaknesses that hinder its direct impact on fostering a healthier food production landscape. This review demonstrates how the risk analysis process, particularly scientific opinions in risk assessment and external factors (economic and political) in risk management, impact food governance and the healthiness of food systems. We find that while external factors play a crucial role in risk management decisions by incorporating non-food safety considerations, they often stem from an imbalance of power favouring major industry and political stakeholders. This imbalance disproportionately influences decision-making, often overshadowing nutritional and health aspects. To address these challenges, we recommend directing research towards filling knowledge gaps and exploring minority scientific findings, and separating external factors from risk management’s decision-making process, to ensure that food governance prioritises public health and healthy food production.